Symptomatic primary Cytomegalovirus infection in a HIV-positive pregnant woman. (December 2014) - Bergin, Sarah; Ferguson, Wendy; Corcoran, Suzanne; Varughese, Allan; Byrne, David; Lawless, Mairead; Eogan, Maeve; Lambert, John S
We describe a case of symptomatic primary Cytomegalovirus infection in a HIV-positive pregnant woman on antiretroviral treatment with a CD4 count >200 × 10 6 /l requiring intravenous ganciclovir. No adverse consequences from ganciclovir or evidence of congenital Cytomegalovirus infection were found.